Factors Affecting the Integration of E-Procurement in the Public Sector of Pakistan with an Emphasis on Combating Corruption - Kumar, Prince; Khan, Abdullah Muhammad; Aziz, Shahid (2023)
The aim of study to investigates the role of e-procurement technologies to mitigate corruption within the public procurement sector of Pakistan due to which E-procurement can’t be implemented. It examines the factors that contribute to corruption probability in government procurement process. The implementation of E-Procurement, within the public sector represents a significant transformation in the country's governance which serves as a strategic response to enhance transparency, accountability, and efficiency in public procurement processes. In the design of E-procurement adoption, three primary factors were taken into consideration to address obstacles: Monopoly power; Information asymmetry; Transparency and accountability. A survey was distributed to 232 procurement specialists and government suppliers; the approach chosen involves the distribution of a well-structured closed-ended questionnaire to enable quantitative assessment, utilizing a convenience sampling method. Obtained informed consent from participants that ensure participants understand the purpose, procedures, potential risks, and benefits of the research project and voluntarily agree to participate. The SPSS software was employed to compile the results of multiple regression models. The findings reveal a substantial 76.9% impact of various variables contributing to adaptation of E-procurement. The result indicates that all three-independent variable: Monopoly power, Information asymmetry, transparency & accountability are creating major resistance in implementation of E-procurement in the government organizations which are the major cause of corruption. This research provides valuable insights into enhancing the efficiency and effectiveness of resources within the public sector. As one of the few studies on this topic, it serves as a foundational piece of literature that can guide future research and policymaking endeavors in Pakistan's public procurement landscape. Ultimately, the successful implementation of E-Procurement has the potential to transform how public funds are managed, ensuring greater accountability, transparency, and efficiency in public sector operations.